Renhed og urenhed i zarathustrismen - Sand, Erik Reenberg (Religionsvidenskabeligt Tidsskrift, 1997)
This paper deals with the relation between the pure and the impure in the late Avestan text Vendīdād. It is shown how, in this religion, there is an almost exact correlation between the cosmic dualism between the good creation of Ahura Mazdā and the evil creation of Angra Mainyu and the pure and the impure. The world is thus split up between the good and the pure beings on the one hand and the evil and the impure on the other. Between these stands man, on the one side good by origin, but on the other struck by evil in the form of death, his main task being to fight impurity and evil in order to make possible the renewal of the original good creation. Finally, the Zoroastrian cosmology and pollution concepts are compared with the typologies presented by Mary Douglás, and it is concluded that, in spite of some drawbacks of her theory, the Zoroastrian material seems to point to her "small group" typology.